MENGENAL SISI KEMANUSIAAN DAN KERASULAN MUHAMMAD BIN ABDULLAH - Rahim, Muhammad Rafi’iy (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
Analisying the personality and journey of the prophet Muhammad is an inexhaustible study. The figure of the prophet Muhammad kept a number of secrets and lessons, especially specifically aspects of humanity and prophethood. While the writings of experts related to the issue have not received much attention from Islamic scholars. This paper elaborates the life history of the prophet Muhammad, with an emphasis on aspects of his humanity and prophethood. Through searching historical data through information from hadiths that were carried out by contextualization, this paper found that the figure of the prophet Muhammad was inseparable from the figure of a highly respected prophet. In addition, it was also found that the prophet Muhammad in his daily life remained inseparable from ordinary people who could make mistakes in world affairs. While as a Prophet, he was awake from mistakes in conveying God’s message. The implication in religion is to require a wise attitude in copying the behavior of the prophet.